POSTPARTUM BLUES AS A PSYCHOLOGICAL DISORDERS IN NEW MOTHER: A CASE REPORT - Fauqo Wildatil Jannah (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Background: Postpartum blues is one type of psychological distress. It can happen when a mother fails in taking in phase. It is a normal peripartum occurrence after delivery. Postpartum blues is usually characterized by several clinical symptoms such as irritability, anxiety, fluctuating mood, etc. Early identification can help in proper treatment. Objective: To identify postpartum blues condition and understand the referral system for maternal problems. Methods: This is a qualitative study with a case report method on postpartum mother which assessed with Edinburgh Postnatal Depression Scale (EPDS) and followed up with maternity needs. Results: Evaluation of maternity need by nursing and midwifery concepts bring a significant average decrease in the value of postpartum blues. In the first screening, the score is 11, and now the score showed <9. Conclusion: Early detection and appropriate intervention by healthcare providers to collaborate on mitigating these interrelated risk factors would be more effective in reducing rates of postpartum blues. Keywords: psychiatric syndrome, postpartum blues, depression, EPDS.